Contrasted patterns in mating-type chromosomes in fungi: Hotspots versus coldspots of recombination. Issue 3 (December 2015) - Idnurm, Alexander; Hood, Michael E.; Johannesson, Hanna; Giraud, Tatiana
Abstract: It is striking that, while central to sexual reproduction, the genomic regions determining sex or mating-types are often characterized by suppressed recombination that leads to a decrease in the efficiency of selection, shelters genetic load, and inevitably contributes to their genic degeneration. Research on model and lesser-explored fungi has revealed similarities in recombination suppression of the genomic regions involved in mating compatibility across eukaryotes, but fungi also provide opposite examples of enhanced recombination in the genomic regions that determine their mating types. These contrasted patterns of genetic recombination ( sensu lato, including gene conversion and ectopic recombination) in regions of the genome involved in mating compatibility point to important yet complex processes occurring in their evolution. A number of pieces in this puzzle remain to be solved, in particular on the unclear selective forces that may cause the patterns of recombination, prompting theoretical developments and experimental studies. This review thus points to fungi as a fascinating group for studying the various evolutionary forces at play in the genomic regions involved in mating compatibility. Highlights: Mating type loci and sex chromosomes are associated with suppressed recombination. Exceptions to recombination suppression are known in the fungi. Some fungal mating systems rely on or include increased recombination frequencies.